2021
DOI: 10.1177/00222437211031243
|View full text |Cite
|
Sign up to set email alerts
|

How Association with Physical Waste Attenuates Consumer Preferences for Rescue-Based Food

Abstract: In an effort to combat food waste, many firms have introduced rescue-based foods (RBF) which are made from ingredients that are safe to eat but would otherwise be wasted, often due to aesthetic deviations or oversupply. Although the benefits to RBF are varied, some firms adopt strategies that highlight waste reduction properties, such as reduced landfill use or lowered impacts on the environment. The current research posits that when firms adopt strategies that highlight physical waste associations with RBF, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 48 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Sustainable brands also elicit risk perceptions, especially about price (Kang & Kim, 2013; Sadiq et al, 2021) and contamination, including fear of disease transmission (Meenakshi, 2020; Meng & Leary, 2021). Contamination risk is particularly detrimental to foods (Monnot et al, 2019): for instance, rescue‐based food can elicit the imagery of waste, spoilage, or deformation of food (de Visser‐Amundson et al, 2021). Also, clothes and products that come in direct contact with the skin are perceived as risky and not hygienic (Meng & Leary, 2021), such as the case of second‐hand products (Becker‐Leifhold & Iran, 2018).…”
Section: Results From the Thematic Analysismentioning
confidence: 99%
“…Sustainable brands also elicit risk perceptions, especially about price (Kang & Kim, 2013; Sadiq et al, 2021) and contamination, including fear of disease transmission (Meenakshi, 2020; Meng & Leary, 2021). Contamination risk is particularly detrimental to foods (Monnot et al, 2019): for instance, rescue‐based food can elicit the imagery of waste, spoilage, or deformation of food (de Visser‐Amundson et al, 2021). Also, clothes and products that come in direct contact with the skin are perceived as risky and not hygienic (Meng & Leary, 2021), such as the case of second‐hand products (Becker‐Leifhold & Iran, 2018).…”
Section: Results From the Thematic Analysismentioning
confidence: 99%
“…Related consumer psychology research has examined people's perceptions of rescue-based food, that is, excess food containing ingredients that are suitable for people to eat that would typically go to waste largely due to aesthetic issues or excess quantities. A study by de Visser-Amundson et al (2021) found that promoting the sustainability benefits of rescue-based food, such as its waste-reduction potential, inadvertently evoked negative and disgusting mental representations such as images of garbage in landfills (de Visser-Amundson et al, 2021), leading to a lower desire to eat such food. By contrast, other research focused on so-called "ugly produce" has found that people will seek to eat these foods when perceptions of aesthetic beauty are expanded (Koo et al, 2019).…”
Section: Perceptions Of Sustainabilitymentioning
confidence: 99%
“…First, research on rescue-based food (RBF) – also sometimes referred to as upcycled food or even “value added surplus food” – is limited despite the widespread issue of food waste (Bhatt et al , 2018; Bhatt et al , 2020). Importantly, as one of the few papers, De Visser-Amundson et al (2021) show that consumers do not have an inherent aversion toward RBF but that marketeers’ actions can, unintentionally, have detrimental effects on consumer demand by evoking waste associations. We build on their work not only by using a last-minute context of rescued meals, but also by showing how product construal and benefit appeals interact to influence consumer decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…We build on their work not only by using a last-minute context of rescued meals, but also by showing how product construal and benefit appeals interact to influence consumer decision-making. While the effects of construal level (Castagna et al , 2021; White et al , 2011) and benefit appeals (De Visser-Amundson et al , 2021; Wu et al , 2017) have been well documented separately in the pro-social domain, research on their combined effects is scarce and shows inconsistent results. Some studies suggest that consumers who are in an abstract mindset are more likely to be interested in sustainable products when the environmental (vs financial) benefits are highlighted, while benefit appeals have no impact on consumers who have a concrete mindset (Goldsmith et al , 2016; Yang et al , 2015).…”
Section: Introductionmentioning
confidence: 99%